2016
DOI: 10.1111/ppl.12451
|View full text |Cite
|
Sign up to set email alerts
|

Alternative oxidase: a respiratory electron transport chain pathway essential for maintaining photosynthetic performance during drought stress

Abstract: Photosynthesis and respiration are the hubs of energy metabolism in plants. Drought strongly perturbs photosynthesis as a result of both diffusive limitations resulting from stomatal closure, and in some cases biochemical limitations that are associated with a reduced abundance of key photosynthetic components. The effects of drought on respiration, particularly respiration in the light (RL ), are less understood. The plant mitochondrial electron transport chain includes a non-energy conserving terminal oxidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 99 publications
2
66
0
Order By: Relevance
“…Since both systems produce a large amount of energy, it is of utmost necessity to maintain coordination between the activities of chloroplasts and mitochondria in the light. 7 The expression of AOXs also is known to be induced by a wide range of biotic and abiotic stresses. 8,3 The induced expression of AOX genes under stress conditions is associated with stress-dependent reactive oxygen species (ROS) production.…”
Section: Genetic Control Of Aox Respirationmentioning
confidence: 99%
See 2 more Smart Citations
“…Since both systems produce a large amount of energy, it is of utmost necessity to maintain coordination between the activities of chloroplasts and mitochondria in the light. 7 The expression of AOXs also is known to be induced by a wide range of biotic and abiotic stresses. 8,3 The induced expression of AOX genes under stress conditions is associated with stress-dependent reactive oxygen species (ROS) production.…”
Section: Genetic Control Of Aox Respirationmentioning
confidence: 99%
“…27 It has been reported that, for several species of monocot and dicot leaves, drought stress can lead to an increase in the transcription of gene(s) encoding AOX, the amount of AOX protein, or the maximum capacity of the AOX pathway to consume electrons. 7 AOX controls respiration, photosynthesis and chlorophyll synthesis during drought to maintain an overall homeostasis and enhance plant lifespan. 7 AOX has also been reported to be responsible for development of cold resistance in winter wheat seedlings, whereas at temperatures below zero AOX activity slightly decreases.…”
Section: Abiotic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, mitochondrial alternative oxidase (AOX) isoforms can be induced by drought in plants, including cowpea, to limit mitochondrial ROS production (Vanlerberghe et al, 2016) (Costa et al, 2010) (Wang and Vanlerberghe, 2013). The plastid terminal oxidase PTOX, a chloroplast homologue of AOX, is induced in some plant species to limit excess electron transfer in the chloroplast during stress (Laureau et al, 2013) (Johnson and Stepien, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Arabidopsis and tobacco (Nicotiana tabacum) clearly revealed a role for AOX in the dissipation of excessive reducing power while maintaining photosynthesis under high-light stress (Florez-Sarasa et al, 2011Dahal et al, 2014Dahal et al, , 2015Vanlerberghe et al, 2016). In Arabidopsis, aox1a knockout plants cannot be complemented by the expression of other isogenes (Strodtkötter et al, 2009;Kühn et al, 2015).…”
mentioning
confidence: 99%